Goal-Directed Transthoracic Echocardiography During Advanced Cardiac Life Support. Issue 4 (August 2015) - Greenstein, Yonatan Y.; Martin, Thomas J.; Rolnitzky, Linda; Felner, Kevin; Kaufman, Brian
<x xml:space="preserve">Abstract</x> Introduction Goal-directed echocardiography (GDE) is used to answer specific clinical questions that provide invaluable information to physicians managing a hemodynamically unstable patient. We studied perception and ability of house staff previously trained in GDE to accurately diagnose common causes of cardiac arrest during simulated advanced cardiac life support (ACLS); we compared their results with those of expert echocardiographers. Methods Eleven pulmonary and critical care medicine fellows, 7 emergency medicine residents, and 5 cardiologists board certified in echocardiography were enrolled. Baseline ability to acquire 4 transthoracic echocardiography views was assessed, and participants were exposed to 6 simulated cardiac arrests and were asked to perform a GDE during ACLS. House staff performance was compared with the performance of 5 expert echocardiographers. Results Average baseline and scenario views by house staff were of good or excellent quality 89% and 83% of the time, respectively. Expert average baseline and scenario views were always of good or excellent quality. House staff and experts made the correct diagnosis in 68% and 77% of cases, respectively. On average, participants required 1.5 pulse checks to make the correct diagnosis. Of house staff, 94% perceived this study as an accurate assessment of ability. Conclusions In an ACLS-compliant manner, house staff are capable of diagnosing management-altering pathologies the majority of the time, and they reach similar diagnostic conclusions in the same amount of time as expert echocardiographers in a simulated cardiac arrest scenario.